(untitled) - Levinson, Warren (New York, 2006)
Save hours of study time, build test taking confidence, and ace the USMLE Step 1 and course exams with most user-friendly, complete, and frequently updated review of medical microbiology and immunology available. There's no faster or more effective way to prepare for the USMLE Step 1 and course exams than Medical Microbiology & Immunology Examination. Completely updated throughout, the Ninth Edition offers a concise, high-yield review of the basic and clinical aspects of bacteriology, virology, mycology, parasitology, and immunology, with an emphasis on the clinical application of microbiology and immunology to infectious diseases.
Keywords: Medical microbiology,Immunology,Vi sinh vật y học,Miễn dịch học